Social Economical Factors of Old People Subjective Quality of Life - Vaznonienė, Gintarė (Sociologija. Mintis ir veiksmas, 2010)
This article is intended to review the evolution of quality of life conceptualization in academic literature as well as to analyze the results of subjective quality of life of old people in Lithuania. The scientific analysis of subjective quality of life (well-being) refers to people’s global judgments about their whole quality of life and life satisfaction also giving special attention to the reactions on different social economical factors influencing their quality of life. The subjective quality of life questionnaire was adopted according to internationally accepted subjective quality of life methodologies. The research was based on self-report questionnaires in Lithuanian old people sample (N=602). Research results reveal significant importance of social economicfactors evaluating whole quality of life and its domains of old respondents.
Keywords: quality of life; subjective quality of life; elderly people; social economical factors